Trans truth and the synodal Church - Burbach, Nicolete (Theology & sexuality, 2023)
The Vatican’s Commission on Spirituality Sub-Group’s 2022 document, Towards a Spirituality for Synodality, offers a vision of a synodal ecclesial life. Central to this vision is the conviction that marginalised groups need to play an equal and active part in that life. This paper reflects on how this inclusion might extend to trans people. It argues that the synodal life of the Church, as envisioned by the CCSG, can include providing a space for the creative overcoming of historical dynamics that alienate trans people from the truths of our own lives, and that the Church fulfils its vocation to synodality in doing so. It concludes by suggesting a model of accompaniment in ‘synodal solidarity’ to facilitate this.